(untitled) (Research, Society and Development, 2020)
The potential of living concrete or bioconcrete as an alternative to regenerate structures is remarkable, and its application to structures that often require a high strength specific concrete such as bridges or tunnels is simply ideal. High weather and stress resistance are some of the characteristics that live concrete has the purpose of offering to solve common structural problems (cracks or cracks). Several factors, such as precarious soils and external agents, can contribute for these pathologies to occur, thinking about this type of problem. Studies have been conducted aiming at a definitive and effective solution, always aiming at the preservation of the environment. This is how the idea of creating a type of concrete with the addition of living organisms, more specifically bacteria, that through their life cycle could regenerate cracks or cracks and guarantee differentiated mechanical properties from ordinary concretes. Besides being extremely efficient once applied, the maintenance of the structures is practically optional, considerably reducing the cost after work, avoiding many poster problems and, of course, extending its useful life. This paper aims to show this new trend in the area of materials.